2016
DOI: 10.1016/j.jval.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Characteristics of Utility Weights for Economic Evaluation of Pediatric Vaccines: A Systematic Review

Abstract: The scarcity of appropriate utility weights for vaccine-preventable infectious diseases in children and a lack of standardization in their use in economic assessments limit the ability to accurately assess the benefits associated with interventions to prevent infectious diseases. This is an issue that should be of concern to those making decisions regarding the prevention and treatment of infectious childhood illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 128 publications
0
11
1
1
Order By: Relevance
“…The HRQoL for EV-A71 HFMD patients has only been reported in one study [ 8 ] which suggested that disability adjusted life years (DALY) incurred by an HFMD episode was 1.76/1000 for mild patients and 3.47/1000 for severe patients. Our HRQoL results are not directly comparable with theirs due to differences in methodology (e.g., in the design of survey instruments and utility measures) [ 26 ]. When compared with the health utility for children who had similar diseases, such as acute rotavirus gastroenteritis with same elicitation instrument, [ 27 ] mild and severe HFMD cases had higher utility score (0.83 and 0.61) than pediatric patients with acute rotavirus gastroenteritis (primary care cases: 0.69–0.78, severe cases 0.08–0.26).…”
Section: Discussioncontrasting
confidence: 56%
“…The HRQoL for EV-A71 HFMD patients has only been reported in one study [ 8 ] which suggested that disability adjusted life years (DALY) incurred by an HFMD episode was 1.76/1000 for mild patients and 3.47/1000 for severe patients. Our HRQoL results are not directly comparable with theirs due to differences in methodology (e.g., in the design of survey instruments and utility measures) [ 26 ]. When compared with the health utility for children who had similar diseases, such as acute rotavirus gastroenteritis with same elicitation instrument, [ 27 ] mild and severe HFMD cases had higher utility score (0.83 and 0.61) than pediatric patients with acute rotavirus gastroenteritis (primary care cases: 0.69–0.78, severe cases 0.08–0.26).…”
Section: Discussioncontrasting
confidence: 56%
“…For example, whilst the NICE Methods Guide is prescriptive for the methods that should be used to generate utilities for adults, limited guidance is given around how to generate, source and model utilities for child and adolescent-specific states. Recent reviews have found that child and adolescent-specific preference-based measures have been used only a handful of times in health technology assessments covering children and adolescents submitted to NICE [64], and published cost-utility analyses for child and adolescent populations [65], and that a large range of diverse methods are used to generate published utilities for children and adolescents [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Este aporte científico, tanto desde el punto de vista médico como económico, es de gran soporte para las decisiones en términos de servicios y economía de salud, ya que brinda una perspectiva social de la población en términos de disponibilidad (16). Así mismo, la evidencia de este tipo de estudios es usada cada vez más por países y autoridades sanitarias (16,17).…”
Section: Introductionunclassified